Pengaruh Media Tata Surya Terhadap Keterampilan Proses Sains Pada Anak Usia 5-6 Tahun di TK Lawiyah Pekanbaru - Nurhanifah, Halima; Purnamasari, Enda; Nurlita, Nurlita (Universitas Pahlawan Tuanku Tambusai, 2024)
Early childhood education can be interpreted as an effort to prepare an environment that can support children's learning, growth and self-development processes. For the personal development of students in PAUD, support from various facilities, means and infrastructure is needed, such as media, classrooms, playrooms, adequate programs and an atmosphere for early childhood education. Early childhood is a child who is developing and growing and has unique characteristics because in children aged 0 to 6 years, all behavior will be formed from early childhood which will have a good effect when the child grows up.Media as an effective learning source is a determining factor in the educational process to achieve educational goals. Based on pre-observations carried out on May 1 2024 through interviews at kindergarten. The results of the interviews prove that there are obstacles during learning activities, namely limited media as a learning resource, making it difficult to convey Solar System material because the media used is still limited and less effective.The hypothesis in this research is that there is a significant influence of solar system media on the science process skills of children aged 5-6 years at Kindergarten Lawiyah Pekanbaru. Type of research: quantitative research using a pre-experimental design method type one group test (initial test, single group final test). The research results show that there is a positive influence of media development on science learning in children aged 5-6 years at Kindergarten Lawiyah Pekanbaru. Before being given treatment and after being given treatment, solar system media on science learning in children provides significant changes. The influence of solar system media on skills. The science process in children aged 5-6 years at Kindergarten Lawiyah Pekanbaru is categorized as low at 12.63%.